Fiscal sustainability of an independent Scotland - Michael Amior; Rowena Crawford; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2013)
In this report, we examine the long-run fiscal pressures that an independent Scotland may face, how these would differ from those facing the UK, and the size of the fiscal consolidation that may be required to put Scotland's public finances on a sustainable path. We do this using a model of the UK's and Scotland's long-run public finances, which is constructed in a similar way to the model that the Office for Budget Responsibility (OBR) uses to produce the forecasts presented in its annual Fiscal Sustainability Report (FSR). Such models seek to answer questions of the type 'What would be the fiscal consequences of continuing into the future with our current set of tax and spending policies?' or 'What scale of tax increases or spending cuts might be required to ensure long-term fiscal balance?'. Despite the considerable uncertainty surrounding the future path of borrowing and debt in Scotland, the main conclusion of our analysis is that a significant further fiscal tightening would be required in Scotland, on top of that already announced by the UK government, in order to put Scotland's long-term public finances onto a sustainable footing. An independent Scottish government might not need to implement such a fiscal consolidation immediately, but these long-run fiscal pressures should certainly form an important part of the backdrop to any discussions about the potential restructuring of Scottish taxation and public spending after independence, if the people of Scotland vote 'yes' to independence in September 2014.
Keywords: 330